Harnessing cerium oxide nanoparticles to protect normal tissue from radiation damage - Baker, Cheryl H. (Translational Cancer Research; Vol 2, No 4 (August 26, 2013): Translational Cancer Research (Nanotechnology in Radiation Research), 2013)
At the onset of radiation exposure, free radicals are formed through ionizing reactions that are then capable of destroying normal tissues. While cells release a level of protective molecules, such as glutathione and metallothionine, they are not capable of blocking all damage, thus resulting in the death of normal tissues and therefore, we must continue to develop strategies to protect normal tissues from radiation-induced damage. One such strategy is the development of radiation protectors. Several compounds have been described, but Amifostine (Ethyol), whose active free thiol metabolite WR-1065 has been shown to prevent both radiation-induced cell death and mutagenesis while facilitating the repair of normal cells remains the only agent currently in clinical use. Major limitations to the clinical use of Amifostine are its short half-life, daily dosing requirements, toxicity based on route of administration, and its cost. Recent studies have shown the effects of engineered cerium oxide (CeO2) nanoparticles for protection against radiation-induced damage in a variety of tissue types. The role of nanoparticles as radioprotectants is a cutting-edge development in decades of scientific interest regarding the protection of normal cells and tissues from radiation. The chemistry of engineered CeO2 nanoparticles supports a potential role as a biological free radical scavenger or antioxidant. The work presented in this review article will address the effectiveness of CeO2 nanoparticles in radioprotection in a variety of cells and in animal models during radiation exposure which will encourage the development of innovative and new approaches to radiation protection, using nanotechnology.